How do technology orientation, organizational learning, market conditions, and firm growth connect? A preliminary analysis on small and medium size hotels in Peninsular Malaysia - Kasim, Azilah; Altinay, Levent (2016)
This paper presents a preliminary analysis on how organizational learning (OL) and market condition (MC) affect the relationship between technology orientation (TO) and growth of small and medium size firms.Using hotels in Peninsular Malaysia as context, the study tested its hypotheses using responses from 254 hotel managers.Regression analysis results indicated that MC has an enhancing effect on the positive and significant relationship between TO and growth/performance of small medium size hotels. Meanwhile, OL only partially mediates the relationship between TO with growth of those hotels.Implications of the findings are discussed at the end of the paper.